Animal Cell Technology: Basic & Applied Aspects Proceedings of the 21st Annual and International Meeting of the Japanese Association for Animal Cell Technology (JAACT), Fukuoka, Japan, November 24-27, 2008 - Kamihira, Masamichi; Katakura, Yoshinori; Ito, Akira; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
Animal cell technology is a growing discipline of cell biology which aims not only to understand the structure, function and behavior of differentiated animal cells, but also to ascertain their ability to be used for industrial and medical purposes. Some of the major goals of animal cell technology include: the clonal expansion of differentiated cells, the optimization of their culture conditions, modulation of their ability for the production of medically and pharmaceutically important proteins and the application of animal cells to gene therapy, artificial organs and functional foods. This volume gives the readers a complete review of the present state-of-the-art research in Japan and other countries where this field is well advanced. The Proceedings will be useful to cell biologists, biochemists, molecular biologists, immunologists, biochemical engineers and to those working in either academic environments or in the biotechnology and pharmacy industries related to animal cell culture.
Keywords: Medicine; Biotechnology; Food science; Life sciences; Cytology; Biomedicine; Biomedicine general; Cell Biology; Life Sciences, general; Biotechnology; Food Science